Numerical analysis of Marangoni convective flow of gyrotactic microorganisms in dusty Jeffrey hybrid nanofluid over a Riga plate with Soret and Dufour effects - Abbas, Munawar; Khan, Nargis; Hashmi, M. S.; İnç, Mustafa (Springer, 2023)
The proposed study explores the effects of thermo-solutal Marangoni convection on radiated Jeffrey fluid in the presence of gyrotactic microorganisms, nanoparticles and dust particles over a Riga plate. The Riga plate is composed of magnets and electrodes organized on a plate. The Lorentz force grows exponentially in the vertical direction because the fluid conducts electricity. The Dufour-Soret effects and activation energy are discussed in the present model. The molten crystal development, the expansion of vapor bubbles during nucleation, thin-film diffusion and semiconductor fabrication are few applications of Marangoni convection. We combined dust particles with microorganisms in present study to enhance the mass transport phenomena. The main objective of this study is to determine the thermal mobility of nanoparticles with C2H6O2\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${\text{C}}_2 {\text{H}}_6 {\text{O}}_2$$\end{document} ethylene glycol as base fluid. For the thermal analysis, Fe3O4\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${\text{Fe}}_3 {\text{O}}_4$$\end{document} and Cu\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${\text{Cu}}$$\end{document} nanoparticles are more effective elements. With the use of new set of similarity variables, the governing PDEs are converted into ODEs, which are then numerically solved using the MATLAB (RKF-45th) technique. The results reveal that the velocity profiles rise for both the fluid and dust phases, while the thermal, microorganism and concentration profiles decline as the Marangoni convection parameter rises. By increasing the value of Marangoni convection parameter up to 10%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$10\%$$\end{document} the values of heat transfer and mass transfer enhance up to 9%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$9\%$$\end{document} and 7.15%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$7.15\%$$\end{document}, respectively.
Keywords: Gyrotactic microorganisms; Jeffrey hybrid nanofluid; Activation energy; Soret and Dufour effects; Marangoni convection; Riga plate